Kecerdasan Buatan: Resiko, Tantangan Dan Penggunaan Bijak Pada Dunia Pendidikan - Rochim, Ahmad Abdul (Universitas Terbuka, 2024)
Abstract: The development of technology has changed many aspects of life, one of which is education. A significant change is the emergence of artificial intelligence, which has become an integral part of the teaching and learning process. This article aims to explore the understanding of artificial intelligence and the risks associated with it in the context of education. The approach used is through a literature study by analyzing relevant scientific articles. The data collected is analyzed to discuss the impact of the dependent use of artificial intelligence in education. The results show several risks associated with the dependent use of artificial intelligence in education, including potential errors and inaccuracies in artificial intelligence systems, moral issues, and psychological impacts. The article also proposes some measures for using artificial intelligence to overcome these risks. This article aims to provide a better understanding of the use of artificial intelligence in education and offer guidance on how to deal with the risks that may arise.